Crop Improvement 2013
DOI: 10.1007/978-1-4614-7028-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium rhizogenes-Mediated Transformation and Its Biotechnological Applications in Crops

Abstract: The history of Agrobacterium-related plant biotechnology goes back for more than three decades with the discovery of molecular mechanisms of crown gall disease in plants. After 1980s, gene technologies began developing rapidly and today, related with the improved gene transfer methods, plant biotechnology has become one of the most important branches in science. Till now, the most important genes related with agricultural affairs have been utilized for cloning of plants with the deployment of different techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 338 publications
(354 reference statements)
0
16
0
Order By: Relevance
“…In this report, embryo-section was proved to be ideal explant for genetic transformation, while no plant generation or extremely low transformation efficiency were observed for hypocotyl and cotyledon explants. Besides A. tumefaciens, A. rhizogenes is also widely utilized to infect various explants, such as hypocotyl, leaf, stem, shoot and cotyledon, to induce transgenic tissues and/or plants 20,45 . Here, our study also showed that all tested explants, including hypocotyl, leaf and shoot, are suitable for A. rhizogenes-mediated transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this report, embryo-section was proved to be ideal explant for genetic transformation, while no plant generation or extremely low transformation efficiency were observed for hypocotyl and cotyledon explants. Besides A. tumefaciens, A. rhizogenes is also widely utilized to infect various explants, such as hypocotyl, leaf, stem, shoot and cotyledon, to induce transgenic tissues and/or plants 20,45 . Here, our study also showed that all tested explants, including hypocotyl, leaf and shoot, are suitable for A. rhizogenes-mediated transformation.…”
Section: Discussionmentioning
confidence: 99%
“…A. rhizogenes-mediated tissue production, an alternative method for A. tumefaciens-mediated transformation, is often used to induce adventitious root development, i.e. hairy roots, at the site of wounding and infection 20,21 . The ability of A. rhizogenes to induce the formation of neoplastic and plagiotropic roots is attributed to its extrachromosomal replicon root-inducing (Ri) plasmid.…”
mentioning
confidence: 99%
“…The high transformation rates of adhesive disk cells is certainly noteworthy. Agrobacteria are known to be attracted to polyphenolic substances exuded by plant roots (Ozyigit et al, 2013). Haustorial sites are also rich in hydroxycinnamic acid derivatives, caffeic acid depsides and other polyphenols (Löffler et al, 1995), which is evident by the rapid browning of infection sites upon their exposure to air (Johnsen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Besides A. tumefaciens, Agrobacterium rhizogenes has become a popular agent for transforming plant genomes (Ozyigit et al, 2013). A. rhizogenes is a soil-borne bacterium infecting many angiosperms and causing them to produce a copious number of roots which became known as the “hairy root syndrome” (Bahramnejad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation